2021
DOI: 10.21608/ejhc.2021.199134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Talent Management Training Program on Head Nurses Leadership Effectiveness

Abstract: Background: Talent management is increasingly discussed in the human resource management and human resource development literature. It is a set of practices that are implemented in organizations and refers to how organizations attract, select, develop and manage employees in an integrated and strategic way. The study aim: To investigate the effect of talent management training program on head nurses leadership effectiveness. Research design: A quasi-experimental research design was utilized. Setting: The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…These results were in agreement with Egyptian studies and Jordan's study, which found that poor statistically significant difference in the pre-test while there was an improvement throughout the post-training phase (Elhanafy & El Hessewi, 2021;Khalil, 2017;Obeidat et al, 2018;Rashed, 2017). The current study was incongruent with the study of Chen & Liu (2019), which aimed to con- The present result was consistent with the study of Saleh et al (2015) and Wiley (2016) b Mann-Whitney test was significant at (α = .05).…”
Section: Min-maxsupporting
confidence: 93%
See 2 more Smart Citations
“…These results were in agreement with Egyptian studies and Jordan's study, which found that poor statistically significant difference in the pre-test while there was an improvement throughout the post-training phase (Elhanafy & El Hessewi, 2021;Khalil, 2017;Obeidat et al, 2018;Rashed, 2017). The current study was incongruent with the study of Chen & Liu (2019), which aimed to con- The present result was consistent with the study of Saleh et al (2015) and Wiley (2016) b Mann-Whitney test was significant at (α = .05).…”
Section: Min-maxsupporting
confidence: 93%
“…Similar results were found in two Egyptian studies that reported that nurses needed to have a human and trustful relationship with their managers. Nurse managers should establish positive human relationships with their nursing staff through caring (AbouHashish & Khatab, 2018; Elhanafy & El Hessewi, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingram and Glod (2016) reported in their study conducted with health institutions in Poland that TM is not applied. In two quasi‐experimental studies, preintervention, it was found that the nurse managers did not have sufficient knowledge about TM (Youssef Elhanafy & Moh Samir El Hessewi, 2021) and the training on TM had an effect on increasing the knowledge and practices of nurse managers on TM (Abdrabou & El‐SayedGhonem, 2020; Youssef Elhanafy & Moh Samir El Hessewi, 2021). Another two studies found that nurses are satisfied with TM practices, and the hospital attracts, develops, motivates, and retains talented employees through the TM process (Ahmed et al., 2019; El Dahshan et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The talent management (TM) appears to be the primary responsibility that organizations are focusing on these days (Dalayga & Baskaran, 2019) [14] . Thus, TM is increasingly being covered in human resource management (HRM) as well as development (Elhanafy & El Hessewi, 2021) [18] . The importance of TM is growing in the healthcare industry, especially in the nursing field.…”
Section: Introductionmentioning
confidence: 99%